Alternative conception of high school students related to the concepts in the simple electric circuit subject matter - K Wardiyah; A Suhandi; A Samsudin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to find out the alternative conceptions of high school students related to concepts in the subject matter of simple electric circuit. The concepts reviewed include the concept of electromotive force (emf), the concept of electric current and the concept of electrical resistance. This research was conducted using quantitative descriptive methods. The number of research subjects was 36 students consisting of 20 female and 16 male, in one of the high schools in the West Bandung district of West Java province. Data were collected by conception test in the form of open essays test related to concepts in the subject matter of simple electric circuit. The results showed that the number of alternative conceptions that high school students had that emerged on each concept were: 1) There were three (3) alternative conceptions that emerged in the concept of electromotive force; 2) There are four (4) alternative conceptions that arise in the concept of electric current, and there are four (4) alternative conceptions on the concept of electrical resistance. These results indicate that the conception that high school students have in relation to concepts in the subject matter of a simple electric circuit still deviates from scientific conception and leads to misconception.